Entrepreneurship with Young People Serving Prison Sentences - Lavandera, Marcos (Ingeniería Solidaria, 2015)
This article is a product of the Extension Project for Entrepreneurs at the Olavarría Engineering Faculty of the Universidad Nacional del Centro de la Provincia de Buenos Aires, Argentina, which focused on providing quality training, broadening and modernizing the offering of professional training, and prioritizing the line of education through cooperative work and entrepreneurship in the framework of social economy among young people serving prison sentences. The research was carried out at the Centro Cerrado Leopoldo Lugones de Azul, with young people under the age of 18 who were on trial or serving prison sentences. 17 youths received 11 systematized visits, at a determined time and day of the week. A space was generated in which six engineering students would share their knowledge about entrepreneurship for two hours with the aim of encouraging the young people to begin new life projects. Entrepreneurs from the community were also present and told of their experiences as a strategy for reinforcing the theoretical concepts and, from there, to pinpoint enterprises through the vocational workshops available at the institution. The most representative result of the project was getting the young people to recognize a different way of learning while identifying other possible ways of living for undertaking new projects.
Keywords: Enterprise; projects; young people; penitentiary centers